2020
DOI: 10.1101/2020.05.23.112946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling the transmission and vaccination strategy for porcine reproductive and respiratory syndrome virus

Abstract: 14 15 In the monitoring of porcine reproductive and respiratory syndrome virus (PRRSv), 16 knowledge about between-farm transmission dynamics is still lacking. Our objective was 17 to assess the relative contribution of between-farm PRRSv transmission routes through a 18 mechanistic epidemiological model calibrated with PRRSv occurrence, identify risk 19 areas, and estimate the impact of immunization strategies in the disease spread. We 20 developed a mathematical model of PRRSv transmission accounting for s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(36 citation statements)
references
References 64 publications
1
34
1
Order By: Relevance
“…As expected, an increase in vaccination coverage resulted in a greater reduction of infectious herds at the end of 52 weeks, with the best results observed at 60 and 80% vaccine coverage. This trend was observed in other studies in Vietnam (21) and the United States of America (38). Due to the high contact rates from large farms to other farms, vaccination of large and medium farms resulted in a high reduction of infectious herds at the end of 52 weeks.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As expected, an increase in vaccination coverage resulted in a greater reduction of infectious herds at the end of 52 weeks, with the best results observed at 60 and 80% vaccine coverage. This trend was observed in other studies in Vietnam (21) and the United States of America (38). Due to the high contact rates from large farms to other farms, vaccination of large and medium farms resulted in a high reduction of infectious herds at the end of 52 weeks.…”
Section: Discussionsupporting
confidence: 81%
“…The model included the spread of PRRS virus via scavenging, sharing breeding boars, and sharing equipment which are very common practices in East African pig farms, including Uganda (10,37). Scavenging was not considered in PRRS simulation models in other countries, making this model unique (21,23,38). Other studies suggested that boar sharing was a critical contributor to the spread of swine diseases where other forms of direct contact (pig trade) have been halted, which was observed in our study (11,14).…”
Section: Discussionmentioning
confidence: 99%
“…Porcine epidemic diarrhoea virus (PEDV) remains endemic in North America (Stevenson, Hoang, et al., 2013; USDA, 2017; Weng et al., 2016); however, based on the data from the Morrison's Swine Health Monitoring Project (MSHMP), the PEDV incidence in the United States has been in decline (Goede et al., 2015; Machado et al., 2019; Perez et al., 2019). Similar to porcine reproductive and respiratory syndrome virus (PRRSV), PEDV epidemic seasonal with most outbreaks occur during colder months (Galvis et al., 2020; Goede & Morrison, 2016; USDA, 2017). The most important clinical signs are vomiting, watery diarrhoea and dehydration in suckling piglets during the weeks of life that lead to a high morbi‐mortality (Annamalai et al., 2015; Madson et al., 2016; Niederwerder & Hesse, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies indicated that limited biosecurity practices and/or the introduction of unexposed gilts increases the risk of virus persisting in farrowing units (Niederwerder & Hesse, 2018). In addition, between‐farm pig movements have been described as the main route of different pathogens including PEDV (Galvis et al., 2020; Lee et al., 2017; Machado et al., 2019; O’Dea et al., 2016; Widgren et al., 2018), with farrowing units being the most likely superspreaders (Lee et al., 2017; Passafaro et al., 2020). In areas of high hog production density, the proximity among farms has been suggested to play an important role in PEDV spread through indirect pathways such as airborne, people, tools, insects or other animals (Alonso et al., 2014; Alvarez et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While our analyses were not aimed to explore the route of transmission events or how viral lineages first entered a population (Rasmussen et al, 2018), they reinforce the importance of PRRSV collateral spread and open the question of how this dissemination is happening. Indeed, a recent work (Galvis, Prada, Jones, & Machado, 2020) showed that for sow farms, more than 50% of the between-farm transmission occurred by proximity among infected TA B L E 3 Number of transmission events that have been originated in farms that belong to the same pig system (local) compared to the events coming from farms integrated into another pig system (external)…”
Section: Within-production Systems Circulation (Local) Versus Introduction Of Prrsv From Commercially Unrelated Farms (External)mentioning
confidence: 99%